Perempuan dalam Pusaran Konflik Afghanistan Pasca Penguasaan Taliban 2021 - Mayasari, Lutfiana Dwi; Lutfiana Dwi Mayasari; Abu Muslim (Center of Gender Studies and Child of State Islamic Institute of Metro, 2025)
The Taliban's success in taking back the Afghan government in August 2021 raised concerns for women in Afghanistan. Even though Taliban spokesperson Zabiullah Mujahid emphasized that the Taliban currently has a moderate ideology, in reality, the threat of domestication, discrimination, and structural alienation as carried out by the Taliban before 2001 continues to threaten the existence of women. This can be seen in various media reports, one of which is the CNN news headline. Through qualitative research, researchers conducted a study to find out how the media depicts the condition of women amidst the Taliban conflict in Afghanistan. Roland Barthes' semiotics is used as an analytical method to determine the meaning of denotation, connotation and myth. The results of the research show that there are three denotational meanings in CNN news headlines about the condition of women in Afghanistan, namely helplessness, resistance, and culminating in gathering international support. The connotation shows that the Taliban's discrimination against women is real. However, they did not accept this discriminatory policy, resulting in various kinds of resistance that attracted international attention. The CNN news headline builds a mythical meaning (message) that the pretext of enforcing Islamic law promoted by the Taliban is just a cover to alienate and discriminate against women. The Taliban's politics towards women actually contradicts the values ​​of Islam as a religion of mercy and grace.